The development of a year five children’s engineering teaching module for hots / Kamaleswaran Jayarajah - Kamaleswaran, Jayarajah (2017)
Currently, there is a new push for early engineering to be included in the Science, Technology, Engineering and Mathematics (STEM) program. Activities integrated with early engineering foster Higher Order Thinking Skills (HOTS) among the children. Based on the previous research, it was clear that Malaysian children were lacking of HOTS. In line with that, this study has designed and developed Children’s Engineering Teaching Module (CETM) to help the science teachers to foster HOTS using the engineering elements among the Year Five primary school children. The theoretical foundation of this study was based on Gagne, Piaget and Vygotsky views. The process of developing CETM using the Isman model was carried out using the modified Delphi technique. The interviews with the experts were carried online. A total of 22 experts were involved in the CETM development. The email responses received from the experts were analysed and classified into four themes. CETM was designed and developed based on these four themes. CETM contains four activities whereby each of the activity represents a specific theme in the Year Five science syllabus. The CETM activities encourages children to use the engineering elements such as cyclic process and design thinking. Apart from that, the CETM activities also encourages children to produce a three-dimensional prototype as a solution for the given challenge. Once the CETM was developed and pilot-tested, the CETM activities were implemented in a primary school in Perak. The findings were based on the children’s sketches during the brainstorming session, written answers, verbal expressions, the ability in testing the prototypes and other interactions in the classroom. In addition, the children were interviewed and observed. Based on the analysis, it was found that children had the ability to justify and evaluate, offer different viewpoints and interacted intellectually either with their teacher or among themselves during the CETM activities. Children were also engaged in the reasoning process, creative thinking and participated in the intellectual discussions while designing the prototypes. In fact, they were able to create strategies which promoted ideas when they were designing the prototypes for CETM activities. Based on the reasoning skills test before and after the implementation of CETM, it was observed that there was improvement for some of the HOTS elements and reasoning skills among the children. Based on the test findings, it was found that the children’s ability to make decision, argue, reason deductively and mechanically has improved. One of the implications of this study is the usage of online interview to obtain the experts’ view from various countries. Apart from that, through the development of CETM, teachers were guided to produce activities which encompasses interdisciplinary fields such as technology, astronomy, ecology and sustainable engineering. Meanwhile children will also gain the experience of using the engineering and designing elements while learning science subject in the classroom.